Low dose recombinant full-length circumsporozoite protein-based Plasmodium falciparum vaccine is well-tolerated and highly immunogenic in phase 1 first-in-human clinical testing. Issue 8 (22nd February 2021) - Friedman-Klabanoff, DeAnna J.; Berry, Andrea A.; Travassos, Mark A.; Cox, Catherine; Zhou, Yingjun; Mo, Annie X.; Nomicos, Effie Y.H.; Deye, Gregory A.; Pasetti, Marcela F.; Laurens, Matthew B.
Highlights: rCSP/GLA-LSQ malaria vaccine was associated with only mild/moderate adverse events. Geometric mean (GM) anti-CSP IgG rose > 4-fold 28 days after 1st dose in all groups. rCSP/GLA-LSQ resulted in ~90-fold rise GM anti-CSP IgG 28 days after 3rd dose. GLA-LSQ, a novel adjuvant, showed favorable safety and immunostimulatory results. Abstract: Plasmodium falciparum circumsporozoite protein (CSP) is a major sporozoite surface protein and a key target of pre-erythrocytic malaria subunit vaccines. A full-length recombinant CSP (rCSP) based strategy could be advantageous, as this antigen includes a region critical to sporozoite cell attachment and hepatocyte invasion. The adjuvant Glucopyranosyl Lipid A-liposome Quillaja saponaria 21 (GLA-LSQ) functions as a TLR4 agonist, promotes antigen-specific TH 1 responses and stimulates cytotoxic T cell production. To date, one study has reported the clinical acceptability of GLA-LSQ. We present interim results of a phase 1 first-in-human dose-escalation clinical trial of full-length rCSP vaccine given with or without GLA-LSQ adjuvant. Participants experienced only mild to moderate related solicited adverse events. The lowest adjuvanted vaccine dose achieved >90-fold rise in geometric mean anti-CSP IgG antibody titer. These favorable safety and immunogenicity results confirm the immunostimulatory capacity of this relatively new adjuvant and support next steps in clinical product development. Trial registration: ClinicalTrials.gov Identifier NCT03589794 (registered 18 July 2018)